2014
DOI: 10.1098/rsbl.2014.0203
|View full text |Cite
|
Sign up to set email alerts
|

Cougars’ key to survival through the Late Pleistocene extinction: insights from dental microwear texture analysis

Abstract: Cougars (Puma concolor) are one of only two large cats in North America to have survived the Late Pleistocene extinction (LPE), yet the specific key(s) to their relative success remains unknown. Here, we compare the dental microwear textures of Pleistocene cougars with sympatric felids from the La Brea Tar Pits in southern California that went extinct at the LPE (Panthera atrox and Smilodon fatalis), to clarify potential dietary factors that led to the cougar's persistence through the LPE. We further assess wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 16 publications
1
46
0
Order By: Relevance
“…All scans were analyzed using SSFA software (ToothFrax and SFrax, Surfract Corporation, www.surfrait.com) to characterize tooth surfaces according to the variables of complexity (Asfc) and anisotropy (epLsar). Complexity is the change in surface roughness with scale and is used to distinguish taxa that consume hard, brittle foods from those that eat softer/tougher ones (Ungar et al 2003(Ungar et al , 2007Scott et al 2005;Prideaux et al 2009;Scott 2012;DeSantis et al 2012DeSantis et al , 2013Haupt et al 2013;Donohue et al 2013;DeSantis and Haupt 2014;DeSantis 2016). Anisotropy is the degree to which surfaces show a preferred orientation, such as the dominance of parallel striations having more anisotropic surfaces-as is typical in grazers and consumers of tougher food items (Ungar et al 2003(Ungar et al , 2007Prideaux et al 2009;Scott 2012;DeSantis et al 2013;DeSantis 2016).…”
Section: Dental Microwear Texture Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…All scans were analyzed using SSFA software (ToothFrax and SFrax, Surfract Corporation, www.surfrait.com) to characterize tooth surfaces according to the variables of complexity (Asfc) and anisotropy (epLsar). Complexity is the change in surface roughness with scale and is used to distinguish taxa that consume hard, brittle foods from those that eat softer/tougher ones (Ungar et al 2003(Ungar et al , 2007Scott et al 2005;Prideaux et al 2009;Scott 2012;DeSantis et al 2012DeSantis et al , 2013Haupt et al 2013;Donohue et al 2013;DeSantis and Haupt 2014;DeSantis 2016). Anisotropy is the degree to which surfaces show a preferred orientation, such as the dominance of parallel striations having more anisotropic surfaces-as is typical in grazers and consumers of tougher food items (Ungar et al 2003(Ungar et al , 2007Prideaux et al 2009;Scott 2012;DeSantis et al 2013;DeSantis 2016).…”
Section: Dental Microwear Texture Analysesmentioning
confidence: 99%
“…Modern faunal specimens were examined in publicly accessible collections housed in the Australian Museum, Museum Victoria, and the Western Australian Museum (see Supplementary Table 13 for all specimen numbers and associated data). DMTA using white-light confocal profilometry and scale-sensitive fractal analysis (SSFA), was performed on all replicas of bilophodont teeth that preserved antemortem microwear, similar to prior work (Ungar et al 2003(Ungar et al , 2007Scott et al 2005;Prideaux et al 2009;Scott 2012;DeSantis et al 2012DeSantis et al , 2013Haupt et al 2013;Donohue et al 2013;DeSantis and Haupt 2014). Vombatids were not included in DMTA, because their tooth morphology is not analogous to the extant and extinct marsupials here examined.…”
Section: Dental Microwear Texture Analysesmentioning
confidence: 99%
“…between certain distantly related taxa), but to document differences in diet when they might not necessarily be expected based on tooth morphology alone. Differences between closely related taxa have been captured, for instance, in bovids (Scott, 2012; Ungar, Merceron, & Scott, 2007), cervids (Berlioz, Kostopoulos, Blondel, & Merceron, 2017), ungulates (Schulz, Calandra, & Kaiser, 2010), feliforms (DeSantis & Haupt, 2014; DeSantis, Tseng, et al, 2017), canids (DeSantis et al, 2015), primates (Scott et al, 2005; Ungar, Grine, & Teaford, 2008), and macropodids (DeSantis, Field, Wroe, & Dodson, 2017; Prideaux et al, 2009). Indeed, many bioarchaeological studies have demonstrated distinctive and predictable diet‐related differences in both gross dental wear and microwear within a single species, Homo sapiens (Rose & Ungar, 1998).…”
mentioning
confidence: 99%
“…As a result, saber-toothed cats (e.g., S. fatalis ), American lions ( Panthera atrox ), dire wolves ( Canis dirus ) and coyotes ( Canis latrans ) experienced dramatic feeding stresses 13 , which led to a more fully and rapid consumption of carcasses (e.g., refs 46 ).…”
Section: Introductionmentioning
confidence: 99%